PRAGMATIC FEATURES OF THE TRANSLATION OF TERMS IN THE FIELD OF ENERGETICS - Rinatovna, Albina (Журнал иностранных языков и лингвистики, 2023)
This article discusses topical issues of translating the terms of a specialized field, which is a heterogeneous system. The issues of understanding the pragmatic aspect of translation as a multidimensional concept are highlighted.